2009
DOI: 10.1038/eye.2009.234
|View full text |Cite
|
Sign up to set email alerts
|

Uveitis-like syndrome and iris transillumination after the use of oral moxifloxacin

Abstract: Iris transillumination and sphincter paralysis is a newly recognized adverse effect of oral moxifloxacin therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
56
0
3

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 6 publications
2
56
0
3
Order By: Relevance
“…Ayrıca kornea endotelinde inflamatuar keratik presipitatlar, ön kamarada ve vitreusta inflamatuvar hücre-ler mevcuttur (12) . Oral moksifloksasin kullanımı sonrası iris transillimunasyonu ve persistan midriyazis ile üveit benzeri bir tablo gelişebilir (13) . Tranos et al (14) yayınladığı bir olgu sunumunda oral klaritromisin kullanımı sonrası bilateral diffüz iris atrofisi gelişen bir hastadan söz etmiştir.…”
Section: Introductionunclassified
“…Ayrıca kornea endotelinde inflamatuar keratik presipitatlar, ön kamarada ve vitreusta inflamatuvar hücre-ler mevcuttur (12) . Oral moksifloksasin kullanımı sonrası iris transillimunasyonu ve persistan midriyazis ile üveit benzeri bir tablo gelişebilir (13) . Tranos et al (14) yayınladığı bir olgu sunumunda oral klaritromisin kullanımı sonrası bilateral diffüz iris atrofisi gelişen bir hastadan söz etmiştir.…”
Section: Introductionunclassified
“…Previous cases have been reported in Turkey (5,6) (51 cases), Netherlands (3,7) (4 cases), Belgium (3,4,6) (4 cases), Spain (2) (one case) and France (8) (one case). We describe the first reported case in the Southern Hemisphere.…”
Section: Introductionmentioning
confidence: 99%
“…Patients typically present with acute and usually severe photophobia, red eye, and ocular discomfort or pain, which sometimes simulates acute bilateral iridocyclitis. Cases often occur after a flulike illness or upper respiratory tract infection, some of them after the use of oral moxifloxacin (2)(3)(4) . Middle-aged women are most commonly affected.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] A few studies have reported other diseases presenting with pigment dispersion and iris transillumination defects. [4][5][6] However, no previous report shows active discharge from an iris epithelial cyst. We describe a case with unusual clinical characteristics including iris cyst formation and pigment showering that led to iris transillumination as well as pupil distortion.…”
mentioning
confidence: 99%